Dopamine-Mediated Graphene Bridging Hexagonal Boron Nitride for Large-Scale Composite Films with Enhanced Thermal Conductivity and Electrical Insulation - Shikun Li; Yutan Shen; Xiao Jia; Min Xu; Ruoyu Zong; Guohua Liu; Bin Liu; Xiulan Huai (Nanomaterials, 2023)
Heat accumulation generated from confined space poses a threat to the service reliability and lifetime of electronic devices. To quickly remove the excess heat from the hot spot, it is highly desirable to enhance the heat dissipation in a specific direction. Herein, we report a facile route to fabricate the large-scale composite film with enhanced thermal conductivity and electrical insulation. The well-stacked composite films were constructed by the assembly of polydopamine (PDA)-modified graphene nanosheets (GNSPDA) and hexagonal boron nitride (BNPDA), as well as bacterial cellulose (BC). The introduction of the PDA layer greatly improves the interface compatibility between hybrid fillers and BC matrix, and the presence of GNSPDA-bridging significantly increases the probability of effective contact with BNPDA fillers, which is beneficial to form a denser and complete “BN-GNS-BN” heat conduction pathway and tight filler–matrix network, as supported by the Foygel model fitting and numerical simulation. The resulting BC/BNPDA/GNSPDA film shows the thermal conductivity and tensile strength of 34.9 W·m−1·K−1 and 30.9 MPa, which separately increases to 161% and 155% relative to the BC/BNPDA film. It was found that the low electrically conductive and high thermal conductive properties can be well balanced by tuning the mass ratio of GNSPDA at 5 wt%, and the electrical conductivity caused by GNSPDA can be effectively blocked by the BNPDA filler network, giving the low electrical conductivity of 1.8 × 10−10 S·cm−1. Meanwhile, the BC/BNPDA/GNSPDA composite films effectively transfer the heat and diminish the hot-spot temperature in cooling LED chip module application. Thus, the present study may pave the way to promoting the industrialization of scalable thermal management devices.